Decline in forced vital capacity in subjects with systemic sclerosis-associated interstitial lung disease in the SENSCIS trial compared with healthy reference subjects - Maher, Toby M.; Bourdin, Arnaud; Volkmann, Elizabeth R.; Vettori, Serena; Distler, Jörg; Alves, Margarida; Stock, Christian; Distler, Oliver (Respiratory Research, 2022)
Background: The forced vital capacity (FVC) of healthy individuals depends on their age, sex, ethnicity and height. Systemic sclerosis-associated interstitial lung disease (SSc-ILD) is characterised by loss of FVC. We compared FVC values in the subjects with SSc-ILD in the SENSCIS trial of nintedanib versus placebo with values from hypothetical matched healthy references. Methods: The SENSCIS trial enrolled subjects with SSc with first non-Raynaud symptom in the prior ≤ 7 years, extent of fibrotic ILD on HRCT ≥ 10%, and FVC ≥ 40% predicted. FVC at baseline and decline in FVC over 52 weeks were compared with FVC values in hypothetical healthy reference subjects matched 1:1 to the subjects in the trial for age, sex, ethnicity and height, determined using equations published by the European Respiratory Society Global Lung Function Initiative. Results: At baseline, mean (SD) FVC was 2460 (737) mL in the nintedanib group (n = 287) compared with 3403 (787) mL in the hypothetical matched healthy references. Mean (SD) FVC was 2544 (817) mL in the placebo group (n = 286) compared with 3516 (887) mL in the hypothetical matched healthy references. Mean (SE) changes in FVC at week 52, i.e., age-related loss of lung function, in the hypothetical healthy references matched to the nintedanib and placebo groups, respectively, were − 26.3 (0.5) mL and − 25.8 (0.5) mL. The difference in the change in FVC at week 52 between the nintedanib group and the hypothetical healthy references was 26.6 mL (95% CI: 1.2, 52.0; p = 0.04). The difference in the change in FVC at week 52 between the placebo group and the hypothetical healthy references was 77.5 mL (95% CI: 51.4, 103.7; p < 0.0001). Conclusions: Subjects with SSc-ILD in the SENSCIS trial had impaired lung function at baseline and experienced further deterioration over 52 weeks. The decline in FVC in the placebo group was four-fold greater than in a hypothetical group of matched healthy references, whereas the decline in FVC in patients who received nintedanib was two-fold greater than in hypothetical healthy references. These data highlight the clinical relevance of the slowing of FVC decline provided by nintedanib. Trial registration Registered 5 November 2015, https://clinicaltrials.gov/ct2/show/NCT02597933.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Connective tissue diseases; Pulmonary fibrosis; Scleroderma; systemic; Vital capacity